Crystal structures of a putative periplasmic cystine‐binding protein from Candidatus Liberibacter asiaticus: insights into an adapted mechanism of ligand binding. (24th May 2019) - Kumar, Pranav; Kesari, Pooja; Kokane, Sunil; Ghosh, Dilip Kumar; Kumar, Pravindra; Sharma, Ashwani Kumar
Abstract : The amino acid‐binding receptors, a component of ABC transporters, have evolved to cater to different specificities and functions. Of particular interest are cystine‐binding receptors, which have shown broad specificity. In the present study, a putative periplasmic cystine‐binding protein from Candidatus Liberibacter asiaticus (CLasTcyA) was characterized. Analysis of the CLasTcyA sequence and crystal structures in the ligand‐bound state revealed novel features of CLasTcyA in comparison to related proteins. One of the unique features found in CLasTcyA structure was the positioning of the C‐terminal extended loop of one chain very close to the substrate‐binding site of the adjacent monomer in the asymmetric unit. The presence of a disulphide bond, unique to Candidatus Liberibacter family, holds the C‐terminal extended loop in position. Analysis of the substrate‐binding pocket of CLasTcyA suggested a broad specificity and a completely different orientation of the bound substrates in comparison to related protein structures. The open conformation for one of the two chains of the asymmetric unit in the Arg‐bound structure revealed a limited open state (18.4°) for CLasTcyA as compared to open state of other related proteins (~ 60°). The strong interaction between Asp126 on helix‐α5 of small domain and Arg82 (bigger domain) restricts the degree of opening in ligand‐free open state. The dissociation constant of 1.26 μm by SPR and 3.7 μm by MST exhibited low affinity for the cystine. This is the first structural characterization of anl ‐cystine ABC transporter from plant pathogen and our results suggest that CLasTcyA may have evolved to cater to its specific needs for its survival in the host. Abstract : Analysis of the crystal structures of a putative periplasmic cystine‐binding protein from Candidatus Liberibacter asiaticus, in ligand‐bound states, revealed unique features compared to related proteins. The open conformation for one of the two chains in the asymmetric unit, in Arg‐bound structure, revealed a limited open state (18.4°) in comparison to the open state of other related proteins (~ 60°).